Development of Loop-Mediated Isothermal Amplification Assay for Detection of Clinically Significant Members of Acinetobacter calcoaceticus–baumannii Complex and Associated Carbapenem Resistance - Sharma, Amit; Gaind, Rajni (Frontiers in Molecular Biosciences, 2021)
Background:Acinetobacter calcoaceticus–baumannii (ACB) complex has emerged as an important nosocomial pathogen and is associated with life-threatening infections, especially among ICU patients, including neonates. Carbapenem resistance in Acinetobacter baumannii has emerged globally and is commonly mediated by blaOXA-23. Clinically significant infections with carbapenem-resistant Acinetobacter baumannii (CRAB) are a major concern since therapeutic options are limited and associated mortality is high. Early diagnosis of both the pathogen and resistance is important to initiate the optimal therapy and prevent selection of resistance. In the current study, a loop-mediated isothermal amplification (LAMP) assay was developed for rapid detection of the ACB complex and carbapenem resistance mediated by blaOXA-23. Methodology: Universal LAMP primers were designed for the detection of significant members of the ACB complex and carbapenem resistance targeting the ITS 16S–23S rRNA and blaOXA-23 gene respectively. The optimal conditions for the LAMP assay were standardized for each primer set using standard ATCC strains. The sensitivity of the LAMP assay was assessed based on the limit of detection (LOD) using different DNA concentrations and colony counts. The specificity of LAMP was determined using the non-ACB complex and non-Acinetobacter species. The results of the LAMP assay were compared with those of polymerase chain reaction (PCR). Results: The optimal temperature for the LAMP assay was 65°C, and the detection time varied with various primers designed. Using the ITS Ab1 primer, LODs of LAMP and PCR assays were 100 pg/μl and 1 ng/μl of DNA concentration and 104 cfu/ml and 108 cfu/ml of colony count, respectively. The LAMP assay was 10- and 104-fold more sensitive than PCR using DNA concentration and colony count, respectively. The LAMP assay was found to be specific for clinically important ACB complex species. Significance of the study: The LAMP assay can be applied for early detection of significant species of the ACB complex from clinical samples and their carbapenem-resistant variants. Depending on the emerging pathogen and locally prevalent resistance genes, the LAMP assay can be modified for detection of colonization or infection by various resistant bugs.